"And then AIDS came along": A life course turning point and sub-cohorts of older gay men. Issue 1 (2nd January 2018) - Tester, Griff
ABSTRACT: Research on life course turning points focuses on heterosexuals. Scholars acknowledge that the early AIDS epidemic was a period of crisis for current older gay men, and that this period has shaped and will likely continue to impact their lives. However, few studies have considered the range of early AIDS-related experiences within this group. In this article, I use a life course perspective and in-depth interviews with 40 gay men (60+) in Atlanta to address the following questions: (1) How did current older gay men's experiences vary during the AIDS years? (2) What social factors shaped this variation? I identified three AIDS-related sub-cohorts, which were defined by how participants' social and spatial relationships to urban gay communities influenced their experiences of personal loss, community loss, personal support, and community support between 1981 and 1996. The results suggest that scholars and service providers interested in how early life experiences impact later life should consider the divergent early AIDS-related experiences within the group "older gay men."